KEBANGKITAN POLITIK KANAN-JAUH DAN DAMPAKNYA BAGI MULTIKULTURALISME DI EROPA1 - Rizky Hikmawan (Dauliyah Journal of Islamic and International Affairs, 2017)
Since 1970s the far right movement began to reappear in Europe. The emergence of the movement became an interesting phenomenon in Europe. This is because the history of the movement that affiliated with facism that leads to World War II. Therefore, the emergence of this movement should be observed considering the thoughts that lead to chauvinism that in turn may lead to racism and xenophobia, which is contrary with democracy. One of the consequences of the emergence of the far right movement is the threat to multiculturalism and the stability in Europe. Today, far right politics become a potential alternative for European society in the midst of economic stagnation and several social issues, including immigration. This paper seeks to explain the background of the far-right politics in Europe, the cause of its rise and its impact on multiculturalism in Europe.